(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The treatment of heart failure with reduced ejection fraction in Vietnam is of great concern, not only reflected in the increased incidence and prevalence but also in the issue of using drug combinations in treatment, this problem, however, becomes more concerning when the European Heart Association recently announced an additional group of drugs that have the ability to improve mortality prognosis in patients with heart failure with reduced ejection fraction [1]. The study conducted a survey on the combination of all four drugs in the treatment of heart failure with reduced ejection fraction at Thong Nhat Hospital from July 2023 to April 2024 Objective: Determine the proportion of heart failure patients with reduced EF who are using all medication groups as recommended by the 2021 European Society of Cardiology guidelines. Methods: Our cross-sectional study was conducted on 87 patients with stable heart failure and reduced EF currently being treated at the cardiology department and clinic of Thong Nhat Hospital from July 2023 to April 2024. Results: The proportion of heart failure patients with reduced EF who are treated with all four medication groups is 40.2%. The main reasons include patients having relative contraindications to the medication groups, patient adherence, and economic issues. Conclusion: The rate of non-adherence among patients is high, thus it is necessary to develop health education communication programs, implement measures to encourage people to participate in health insurance, and increase the use of full treatment once contraindications are resolved.